Child Abuse in Psychosocial Aspects and Parenting Patterns: A Study of Parents as Perpetrators - Erly Yunita; Wiwik Sulistyaningsih (Universitas PGRI Yogyakarta, 2026)
The increasing incidence of child violence in the Special Capital Region of Jakarta highlights the need to understand the psychological mechanisms underlying parents’ abusive behavior. This study examined the psychosocial dynamics of parents who perpetrate child abuse using Abidin’s Parenting Stress Model as the theoretical framework. A mixed-methods phenomenological design was employed involving five parents of children aged 5-13 years who had engaged in abusive behavior. Data were collected through in-depth interviews, observation, documentation, and psychological assessment using the Parenting Stress Scale (PSS) and Depression Anxiety Stress Scale (DASS-21). All participants (100%) demonstrated high to very high parenting stress (PSS = 42–50). Emotional stress was the dominant dimension (M = 24.0; severe to extremely severe). Parenting stress showed a very strong correlation with emotional stress (r = 0.86). Factor analysis revealed a single latent construct, Integrated Parenting Distress, explaining 78% of the variance. Qualitative findings indicated that violence emerged as a reactive caregiving response driven by emotional exhaustion, negative child perception, and intergenerational normalization of harsh discipline. Child abuse is therefore better understood as a manifestation of integrated psychological pressure within the parenting system rather than a reaction to child behavior alone. The findings support family-based preventive interventions emphasizing parental emotion regulation and inform urban child-protection policy development. Keywords: child abuse, parenting stress, psychosocial dynamics